2020
DOI: 10.1097/psy.0000000000000904
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depressive Symptoms Among Pregnant and Postpartum Women in China During the COVID-19 Pandemic

Abstract: Objective: According to recent studies, the COVID-19 pandemic has been associated with an increased risk of mental health problems across many subpopulations including pregnant and postnatal women. This study examined the prevalence and correlates of depressive symptoms (depression hereafter) in Chinese pregnant and postpartum women during the COVID-19 pandemic. Methods: This was a multicenter, cross-sectional study comprising 1309 pregnant and postpartum women across 12 provinces in China during the COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 29 publications
4
40
1
Order By: Relevance
“…One reason for this difference may be the time difference in data collection. Two previous studies (Bo et al, 2021;Jiang et al, 2021) Meanwhile, the present study found that the prevalence of CAD remained unchanged during the perinatal period. The prevalence of "anxiety only" in the first trimester of pregnancy was lower, and that in the third trimester, it was higher.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…One reason for this difference may be the time difference in data collection. Two previous studies (Bo et al, 2021;Jiang et al, 2021) Meanwhile, the present study found that the prevalence of CAD remained unchanged during the perinatal period. The prevalence of "anxiety only" in the first trimester of pregnancy was lower, and that in the third trimester, it was higher.…”
Section: Discussionsupporting
confidence: 62%
“…Jiang et al (2021) found that between February 5, 2020, and February 28, 2020, 18.1% of pregnant women in China suffered from anxiety and 45.9% suffered from depression (Jiang et al, 2021). Likewise, Bo et al (2021) found that 27.43% of pregnant and postpartum women in China experienced depression between February 22, 2020, andMarch 10, 2020. In the United States, 43.3% of the pregnant women reported moderate to severe anxiety symptoms at the end of April 2020 (Preis et al, 2020), while in Italy, 44.2% of postpartum women experienced depression between March 8, 2020, and June 15, 2020 (Ostacoli et al, 2020). A meta-analysis of 23 studies conducted with 20,569 pregnant and postpartum women during the COVID-19 pandemic found that the prevalence rates of anxiety and depression among the pregnant women were 37% (95% CI: 25-49%) and 31% (95% CI: 20-42%), respectively and the prevalence rate of depression among the postpartum women was 22% (95% CI: 15-29%) (Yan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, general conflict, poor family functioning and martial distress emerged as significant risk factors for perinatal anxiety during the pandemic ( 56 , 72 , 74 , 81 , 89 , 98 , 116 , 117 , 128 ). Pregnant women's own health anxiety ( 81 , 98 , 103 , 117 , 118 , 129 ) and partner's perceived fear of COVID-19 ( 116 ) were understood to be contributing to pregnant women's increased anxiety and preventative behavior such as increased hygiene practices and social distancing ( 62 , 71 , 116 , 134 ). Women strictly adhering to the rules and safety recommendations reported greater symptoms ( 98 ).…”
Section: Resultsmentioning
confidence: 99%
“…Women who did not have information about the effect of COVID-19 on pregancy were at higher risk of anxiety ( 110 ). Delay in or cancellation of planned informal support and reduced prenatal care were associated with an increase in depressive and anxiety symptoms ( 57 , 81 , 96 , 98 , 103 , 129 ). Women who accessed prenatal care information ( 121 ) and perceived strong support from healthcare staff ( 67 ) were at significantly lower risk of psychological distress.…”
Section: Resultsmentioning
confidence: 99%
“…In Beijing, routine post-natal home visits were replaced by telephone consultations. This effectively protected pregnant and postpartum women from infection, but the effects of these policies on their psychological status and wellbeing are unknown [ 11 ]. Since stress and anxiety in the postpartum period can negatively impact both mother and infant [ 12 ], it is important to understand the psychological repercussions of this pandemic and lockdown on maternal health.…”
Section: Introductionmentioning
confidence: 99%